Inconsistency of the 'spin-3/2 gauge invariant' interaction of Rarita-Schwinger fields - Badagnani, Daniel (2017)
We perform the Dirac quantization of Rarita-Schwinger fields interacting with a spinor and the first derivative of a pseudoscalar field. We achieve the calculations for two forms of this interaction: first we review the conventional coupling of lowest derivative order, reproducing the well known inconsistencies in its anticommutator algebra. Then, we perform the analysis on the next order term popularly known as 'spin-3/2 gauge invariant interaction', which is claimed to be free of these inconsistencies. Nevertheless we find that the direct application of the Dirac formalism leads to inconsistencies in complete analogy to the previous case. This is of high relevance in the particle phenomenology field, where these interactions are used to interpret experimental data involving δ(1232)resonances.